Feedback : Falling flat. (1st August 2020) - Stoter, Larry; Kneath, Trevor; Thomas, David V; Beatty, Mike; Fitch, Christopher; Vos, Johan; Finney, John
Abstract: In response to Rachel Brazil's feature article "Fighting flat-Earth theory" (July pp35–39), in which she explores why the "shocking" notion that the Earth is not a sphere is increasingly taking hold and how the physics community should best respond.